(untitled) (Research, Society and Development, 2025)
Prenatal care is defined as continuous monitoring of pregnant women, from the confirmation of pregnancy until the moment of delivery, aiming to ensure the adequate development of the pregnancy. This study aims to analyze adherence to the prenatal program in the city of Codó, Maranhão, focusing on the number of consultations carried out in the municipality in comparison with that recommended by the Ministry of Health. Considering that prenatal care is essential for reducing maternal and child morbidity and mortality, specific difficulties are noted in Maranhão, where adherence rates are lower than the national average. The research is of an ecological, observational and descriptive epidemiological nature, using data from the Department of Information Technology of the Unified Health System (DATASUS) from 2019 to 2023, addressing the number of consultations carried out. Data on the frequency of pregnant women who attend the minimum number of consultations are observed, correlating data with factors of race, age group and level of education, and are used to outline the panorama of the Prenatal Program in Codó and the profile of pregnant women attended. The importance of this study is due to the lack of specific local research that contributes to improvements in prenatal care, aiming to reduce maternal and neonatal complications and deaths in the municipality.